1996
DOI: 10.1254/jjp.72.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toborinone (OPC-18790), a New Positive Inotropic Agent, on Action Potential in Guinea Pig Sinoatrial Node: Compared with Milrinone and E-4031

Abstract: ABSTRACT-The effects of toborinone ([(±)-6-[3-(3,4-dimethoxybenzylamino)-2-hydroxypropoxy]-2(1H)-quinolinone], OPC-18790), milrinone and E-4031 (1-(2-(6-methyl-2-pyridil)-1-ethyl)-4-(4-methanesulfonylamino-l-benzoyl)piperidine dihydrochloride) on membrane potential were examined in isolated guinea pig sinoatrial node preparations. Toborinone, a new positive inotropic agent, prolonged cycle length (CL), depolarized maximum diastolic potential (MDP) and decreased maximum upstroke velocity (Vmax) and action poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…This is different from what we have observed in the mouse in which Mil and Rol each had similar stimulatory effects on AP frequency and where the stimulatory effect of EHNA, although smaller than Mil and Rol, was still robust. Other studies have also shown that PDE3 inhibitors increase SAN AP frequency in rabbits [35] and guinea pigs [36]; however, these studies did not compare these effects with inhibitors of other PDE families. Our data showing that PDE3 and PDE4 inhibitors can similarly increase AP frequency and I Ca,L in mouse SAN myocytes are consistent with studies showing these inhibitors also increase beating rate in mouse and rat atrial preparations [37].…”
Section: Discussionmentioning
confidence: 89%
“…This is different from what we have observed in the mouse in which Mil and Rol each had similar stimulatory effects on AP frequency and where the stimulatory effect of EHNA, although smaller than Mil and Rol, was still robust. Other studies have also shown that PDE3 inhibitors increase SAN AP frequency in rabbits [35] and guinea pigs [36]; however, these studies did not compare these effects with inhibitors of other PDE families. Our data showing that PDE3 and PDE4 inhibitors can similarly increase AP frequency and I Ca,L in mouse SAN myocytes are consistent with studies showing these inhibitors also increase beating rate in mouse and rat atrial preparations [37].…”
Section: Discussionmentioning
confidence: 89%
“…An earlier observation by Tsien et al in Purkije fibers provided a clue that the level of cAMP in pacemaker cells was regulated by basal PDE activity, because various PDE inhibitors produced a marked increase in the DD slope and shortened AP plateau, mimicking effects of cAMP injection [25]. Later, several studies demonstrated that, similar to Purkinje fibers, suppression of PDE activity in isolated SA node [26-28] produced an increase in cAMP level [26] and an augmentation of the DD slope [27, 28] that resulted in a marked acceleration of the spontaneous beating rate. The extent of PDE-dependent control of the basal cAMP level, and of spontaneous firing of isolated rabbit SANC, has recently been demonstrated: inhibition of total PDE activity by a broad-spectrum PDE inhibitor, IBMX, produces a 9-fold increase in the cAMP level and ~50% increase in the SANC spontaneous beating rate (both effects being greater than those of the saturating concentration of β- AR agonist, isoproterenol [29].…”
Section: The Basal Camp Level Is Linked To Spontaneous Beating In mentioning
confidence: 99%
“…Inhibition of PDE3 causes sinoatrial tachycardia in guinea pigs, 7 rabbits, 5,8 dogs 9 and humans. 10 PDE4 is the dominant PDE isoform in the murine heart, 6 and inhibition of either PDE3 or PDE4 produces sinoatrial tachycardia in mice 11 and rats.…”
Section: Introductionmentioning
confidence: 99%